2003
DOI: 10.1128/jvi.77.5.2832-2842.2003
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative Role of the Human Papillomavirus Type 16 E5 Gene during the Productive Stage of the Viral Life Cycle

Abstract: Human papillomaviruses (HPVs) are small circular DNA viruses that cause warts. Significantly, infection with high-risk anogenital HPVs, such as HPV type 16 (HPV16), is associated with human cancers, specifically cervical cancer (50). The life cycle of HPVs is intimately tied to the differentiation status of the host epithelium and has two distinct stages: the nonproductive stage and the productive stage. The nonproductive stage of the viral life cycle occurs in the basal compartment of the host epithelium wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
144
1
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 151 publications
(153 citation statements)
references
References 48 publications
(44 reference statements)
6
144
1
2
Order By: Relevance
“…The E5 stimulates the transforming activity of the epidermal growth factor receptor resulting in increased cell proliferaction (Pim et al 1992). In a raft culture model, the E5 was shown to support cellular DNA synthesis in suprabasal cells and neither viral late gene expression nor epithelial differentiation was affected by the E5 (Genther et al 2003). The E5 protects human foreskin keratinocytes from ultraviolet B-irradiation-induced apoptosis .…”
Section: E5 Proteinmentioning
confidence: 97%
“…The E5 stimulates the transforming activity of the epidermal growth factor receptor resulting in increased cell proliferaction (Pim et al 1992). In a raft culture model, the E5 was shown to support cellular DNA synthesis in suprabasal cells and neither viral late gene expression nor epithelial differentiation was affected by the E5 (Genther et al 2003). The E5 protects human foreskin keratinocytes from ultraviolet B-irradiation-induced apoptosis .…”
Section: E5 Proteinmentioning
confidence: 97%
“…It has also been shown that E5 alters the growth and differentiation of stratified epithelia and induces epithelial tumors at a high frequency in mice (Genther Williams et al, 2005). Moreover, important functions in late stages of viral replication have been suggested (Fehrmann et al, 2003;Genther et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…HPV perturbs multiple aspects of this differentiation program including the withdrawal of cells from the cell cycle and the expression of differentiation-specific cellular genes. Most notably, suprabasal cells that harbor HPV genomes undergo DNA synthesis and have delayed expression of differentiation-specific proteins (11,12,16,24). These changes induced by the virus are thought to be critical for the synthesis of viral genomic DNA and its encapsidation to form progeny virus (24).…”
mentioning
confidence: 99%